2002
DOI: 10.1016/s1044-0305(02)00395-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of local anesthetic-cyclodextrin non-covalent complexes using capillary electrophoresis and electrospray ionization mass spectrometry

Abstract: Non-covalent complexes between three derivitized cyclodextrins (CD's) and six local anesthetics were studied using capillary electrophoresis (CE) and electrospray ionization mass spectrometry (ESI-MS). The CE study was performed using the complete filling technique (CFT). A comparison between the migration data from CE and ESI-MS inclusion complex peak abundances was made representing the association between local anesthetics and CD's in the solution and the gas phase, respectively. The results from this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Non-covalent complexes between three different cyclodextrins (CD) and six local anaesthetics were studied using capillary electrophoresis (CE) and electrospray ionisation mass spectrometry (ESI-MS) [101].…”
Section: Capillary Electrophoresismentioning
confidence: 99%
“…Non-covalent complexes between three different cyclodextrins (CD) and six local anaesthetics were studied using capillary electrophoresis (CE) and electrospray ionisation mass spectrometry (ESI-MS) [101].…”
Section: Capillary Electrophoresismentioning
confidence: 99%
“…Therefore, combining MEPS and CE can provide interesting advantages. Local anesthetics and their metabolites have so far been determined by CZE [23][24][25][26][27][28], EKC [12,[29][30][31][32] and NACE [26,[33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Fax: +81-795-23-5793; E-mail: n.yamane@jclbio.com Abbreviations: ESI-MS, electrospray ionization mass spectrometry; CD, -cyclodextrin; PG, prostaglandin; MALDI-TOFMS, matrix-assisted laser desorption/ionization time-of-flight mass spectrometry; Glc-CD, glucosyl-CD; Gal-CD, galactosyl-CD; Man-CD, mannosyl-CD; Mal-CD, maltosyl-CD; MM, molecular mechanics; MO, molecular orbital etry was first reported in 1991. 13) Inclusion complexes of amino acids, [14][15][16][17][18][19] peptides 16,20,21) and drugs [22][23][24][25][26] with CDs have been studied by electrospray ionization (ESI). ESI-MS has been used to detect the ions of intact noncovalent inclusion complexes.…”
mentioning
confidence: 99%
“…The capillary electrophoresis migration time shift was utilized in order to prove that the ions of true non-covalent complexes had been detected. 24,26) Srinivasan et al have reported that there was correlation between association constants calculated from differences in migration time shifts and peak height ratios for CDs and their complexes obtained by LC/ESI-MS measurements. The results showed that CD-barbiturate complexation behavior in the gaseous phase was similar to that in the solution phase.…”
mentioning
confidence: 99%